Water balance of goats in Jeneponto - South Sulawesi under sunlight exposure and water restriction - Rahardja, Djoni Prawira (Indonesian Journal of Animal and Veterinary Sciences, 2007)
Water balance of 5 does of Kacang goat of Jeneponto was studied under the condition of sunlight exposure and water restriction. The study was conducted in dry season with 4 consecutive treatments of 10 d with 4-5 d of adjustment period between two consecutive treatments: (1) indoor and unrestricted water; (2) indoor and restricted water; (3) 10 h outdoorâand unrestricted water; (4) 10 h outdoor â restricted water. The maximum air temperature of outdoor was 39.3OC, and it was 30OC in the indoor environment. In all treatments, the animals were placed in the individual crates. The plasma volume of the goats was higher under sunlight exposure, but it decreased by water restriction, while hematocrite value indicated a reverse responses. Sunlight exposure did not significantly decrease the intake and digestion of organic matter, but water restriction affected significantly and this effect was higher under sunlight exposre. The proportions of water loss through every avenue were maintained relatively constant either under water restriction or sunlight exposure in which the respration rate increased significantly. The findings suggest that sunlight exposure with unrestricted water resulted in a positive water balance without a significant change in organic matter intake and utilization. Water restriction resulted in a negative water balance, reducing organic matter intake and utilization. As the adaptive mechanisms, the goat appeared to be able to withstand in the harsh environment of Jeneponto by expanding plasma volume, increasing body temperature and respiration rate. Key Words: Goat, Water Balance, Sunlight Exposure, Water Restriction, Digestion